Influência do método de avaliação no diagnóstico da dor muscular de início tardio após corrida em declive - Leopardi, Júlia Padilha [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Several methods are used towards delayed onset muscle soreness appraisal. This study's goal was to investigate, amongst three commonly adopted methods, which one would be the most effective (the one that shows higher values) in the quantification of this phenomenon. 10 male subjects, of age 22.8 ± 3.1 years old, weight 80 ± 12.4 kg, height 174 ± 0.07 cm, without recent experience with strength training (lower limbs) and/or running took place in this study. All subjects carried out a muscle damage induction protocol, which consisted of 30 minute downhill running (-16% or -9.09º) at 80% speed compared to their maximum oxygen consumption. Muscle damage determinants such as isometric peak torque, knee joint range of motion and circumference of the medial portion of the thight were measured before, during, 24, 48, 72 and 96 hours after downhill running. The subjective pain perception was measured simultaneously with the other determinants through three different tests: sitting on and getting up of a chair; climbing and descending from a 45cm step; and self thigh palpation. After going through all subjective pain perception tests, the subjects filled out a visual analog scale with their perception of pain. Muscle damage changes over time were compared through variance analysis (ANOVA) one way for repeated measures. Subjective pain perception values obtained in all three different tests were compared through two way ANOVAs for repeated numbers. The significance level adopted in this study was z ≤ 0.05. The results showed that the step test was the on which better evaluated the delayed onset muscle soreness. No significant differences were found through the ADM and CIR recovery markers. Downhil running determined reduced of PTI (~22.4%). Significant links between pain were obtained for both subjective pain perception tests starting at 24 and 48 hours, where the highest registered average happened in the step test after 48h, with high...

Diversos são os métodos utilizados na avaliação da dor muscular de início tardio (DMIT). O presente estudo teve como objetivo investigar, entre três métodos comumente adotados, qual seria o mais eficiente (apresentaria valores maiores) na quantificação desse fenômeno. Participaram do estudo 10 voluntários do sexo masculino de 22,8 ± 3,1 anos, 80 ± 12,4 kg, e 174 ± 0,07 cm respectivamente e sem experiência recente com treinamento resistido (membros inferiores) e/ou de corrida. Todos os indivíduos realizaram um protocolo de indução de dano muscular (DM) que consistiria de 30 minutos de corrida em declive (CD) (-16% ou -9,09º) a 80% da velocidade referente ao seu consumo máximo de oxigênio (IVO2máx). Marcadores de DM como o pico de torque isocinético (PTI) (60º.s-1), amplitude de movimento da articulação do joelho (ADM) e circunferência da porção medial da coxa (CIR) foram coletados antes, durante, 24, 48, 72 e 96 horas após a sessão de CD. A percepção subjetiva de dor (PSD) foi coletada nos mesmos momentos que os demais marcadores por meio de três diferentes testes: sentar e levantar de uma cadeira; subir e descer em um step de 45 cm; e auto palpação da coxa. Após a realização de todos os testes de PSD, os voluntários preencheram uma escala de análogos visuais com o valor percebido de dor. Mudanças ao longo do tempo nos marcadores de DM foram comparadas por meio de análises de variância (ANOVA) one-way para medidas repetidas. Os valores de PSD obtidos nos três diferentes testes foram comparados por meio de ANOVAstwo-way para medidas repetidas. O nível de significância adotado no presente estudo foi de z ≤ 0,05. Não foram encontradas diferenças significativas ao longo da recuperação para os marcadores de ADM e CIR. A corrida em declive determinou queda do PTI (~ 22,4%). Foram encontradas correlações significativas de aumento de dor para ambos os testes de PSD a partir de 24 e 48 horas, onde...
Keywords: Medicina esportiva; Mialgia; Corrida; Musculos - Ferimentos e lesões; Dor; Avaliação - Metodologia